An examination of the studies on foreign language teaching in pre-school education: a bibliometric mapping analysis. Issue 3 (4th March 2022) - Yilmaz, Rabia Meryem; Topu, Fatma Burcu; Takkaç Tulgar, Ayşegül
Abstract: This study aims to provide a bibliometric mapping analysis of the studies on foreign language teaching in early childhood education in Web of Science. A total of 638 studies were reached however 596 studies were selected for the analysis. For bibliometric analysis, VOSViewer programme was used in order to reveal the most used keywords, words in the abstracts, citation analyses and co-citation analyses in the studies. In addition, whether any technology was adopted in the studies was examined within 76 studies. The results showed that the most used keywords were English language learning, bilingualism, English as a second language, and English learners. The most used words in the abstracts were teacher, acquisition and effect. Bialystok and Cummins, are the most cited authors in this field. The most cited journals are Journal of Educational Psychology and Applied Psycholinguistics. The studies have been mostly published in Spain, Sweden, and Israel. In addition, it is observed that the studies started in 2012 mainly in the United States, Canada, England and Germany. When technology use in the studies was examined, ICT in education, multimedia, digital technologies, instructional technology, technology integration were used in the studies. This study provides a guide for new studies, to identify the trends in the field and to compare the existing research on the topic. Consequently, it is suggested that future researches need focusing more on the pedagogical aspects and testing whether teaching environments supported by new technologies contribute to foreign language education.